Approaches to carrier testing and results disclosure in translational genomics research: The clinical sequencing exploratory research consortium experience. Issue 6 (21st August 2018) - Porter, Kathryn M.; Kauffman, Tia L.; Koenig, Barbara A.; Lewis, Katie L.; Rehm, Heidi L.; Richards, Carolyn Sue; Strande, Natasha T.; Tabor, Holly K.; Wolf, Susan M.; Yang, Yaping; Amendola, Laura M.; Azzariti, Danielle R.; et al.
Abstract: Background: Clinical genome and exome sequencing (CGES) is primarily used to address specific clinical concerns by detecting risk of future disease, clarifying diagnosis, or directing treatment. Additionally, CGES makes possible the disclosure of autosomal recessive and X‐linked carrier results as additional secondary findings, and research about the impact of carrier results disclosure in this context is needed. Methods: Representatives from 11 projects in the clinical sequencing exploratory research (CSER) consortium collected data from their projects using a structured survey. The survey focused on project characteristics, which variants were offered and/or disclosed to participants as carrier results, methods for carrier results disclosure, and project‐specific outcomes. We recorded quantitative responses and report descriptive statistics with the aim of describing the variability in approaches to disclosing carrier results in translational genomics research projects. Results: The proportion of participants with carrier results was related to the number of genes included, ranging from 3% (three genes) to 92% (4, 600 genes). Between one and seven results were disclosed to those participants who received any positive result. Most projects offered participants choices about whether to receive some or all of the carrier results. There were a range of approaches to communicate results, and many projects used separate approaches for disclosing positive and negative results. Conclusion: Future translational genomics research projects will need to make decisions regarding whether and how to disclose carrier results. The CSER consortium experience identifies approaches that balance potential participant interest while limiting impact on project resources. Abstract : The clinical sequencing exploratory research (CSER) consortium sought to understand the variability in approaches to identifying and disclosing carrier results. The broad range of experiences across 11 of the CSER projects allowed us to distill key considerations important for guiding future translational genomics research projects that will inform decisions regarding whether and how to disclose carrier results. This research may in turn help to guide policy decisions about clinical services.